Repository of Basic Digital Skills for Moroccan Doctoral Students â€œUniversity Case of Study :Hassan II Casablancaâ€ - Redouane Fikri; Malika Tridane; Said Belaaouad (Iraqi Journal of Science, 2021)
Being a doctoral student is not easy because it presupposes having a number of technical skills, among which digital skills, defined by the European Commission (2006) as "the safe and critical use of the technologies of the society of the information". and the variety of digital use in the personal and professional context, allows us to ask the question that any doctoral student should master and acquire in terms of digital skills? And on what basis can we define these skills?In this work we expect to develop a baseline of digital skills, is a document that includes the set of essential digital skills that represents a fundamental tool for the doctoral student who can in no way bypass it. And for this, we conducted interviews with about thirty university professors from different faculties of Hassan II University inCasablanca to arrive to a draft of this reference system, then we proceeded to its validation with a second group of 45 teachers in the same university, while studying the correlations existing between the degree of importance of the fields of numerical competences and the belonging to a faculty of the university in question using the khi2 test.